Education on Social Security Protection Law for Fishermen (Case Study of Fishermen in Cilacap Regency) - Desi Zahara; Herlita Eryke (International Journal on Integrated Education, 2026)
This article discusses the education of legal protection regarding the social security rights of fishermen in Indonesia, particularly related to BPJS Employment participation. A case study was conducted in Cilacap Regency to examine the disputes faced by fishermen in accessing social security benefits. The research results show that the lack of socialization, administrative obstacles, and limited access are the main factors hindering social security protection for fishermen. The government and BPJS Employment need to enhance education, coordination, socialization, and simplification of procedures so that legal protection can run effectively and sustainably. This article provides knowledge about legal education on a policy aimed at strengthening social security protection for fishermen to enhance their welfare and social security.